Effects of Small Business Support Projects: Evidence from Korea - Lee, Jin Kook (KDI Journal of Economic Polilcy, 2020)
On average, small business support projects appear to improve beneficiary sales, and the growth effect is obvious when supporting young or growing firms. However, the effect is largely offset by sales reductions due to overcrowding. Small business support projects must be operated in two ways to alleviate the overcrowding of businesses in a few industries and to enhance the overall effectiveness of the support programs.
Keywords: Small Business Owner; SME; Support Policy; Support Project; Overcrowding